How does the Taylor Rule affect the economy of Kazakhstan? - Tolepbergen, Zh.; Zhadiger, N. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
This paper examines the impact of the Taylor Rule on the economy of Kazakhstan, a developing country in Central Asia. The Taylor Rule is a popular rule used by many countries to guide their economies, including the National Bank of Kazakhstan. However, its impact on the Kazakhstani economy has not been fully studied. This study employs a quantitative research method using time series data from 1994 to 2022 on key macroeconomic variables such as GDP, inflation, and interest rates. Additionally, the study found that the Taylor Rule had a significant impact on the revealing the interest rate of Kazakhstan. This paper also describes the importance of inflation targeting and its relationship with the Taylor Rule. This study summaries that while the Taylor rule is a useful guideline for monetary policy, it has limitations.
Keywords: Taylor Rule, macroeconomic variables, GDP, inflation, interest rate